National Treatment at Investment at Different Levels of Public Administration: Considerations for Policy Makers - Elena Vasilyevna Zhiryaeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article has identified the right subnational interpretation of the principle of national treatment (NT) as a cornerstone determining the policy flexibility of subnational authorities. The purpose is to analyse measures of national and subnational authorities affecting the application of the principle of NT vis-à-vis the foreign investor, which allows to recommend certain approaches to investment policy making at the subnational level. The following issues are discussed in the article: concepts of foreign investors and foreign investment in the Russian Federation; NT in bilateral investment agreements; NT of investment in the context of the WTO agreements; a framework for the description of NT at the subnational level; classification of exceptions from NT; exceptions from NT according to GATS obligations; NT at the subnational level. In the Russian Federation the foreign investor has full legal protection equal to the protection of local firms if it is a legal entity in which the foreign shareholder owns at least 10%, but no more than 20% of the authorized capital, or if the foreign investor does not create a new legal entity, but opts for a branch or a representation office. The model bilateral investment treaty of the Russian Federation follows approaches similar to those of developed countries. Questions were identified which should be answered during the investment policy making at the subnational level: For what kind of investors and how is market entry regulated? What represents post-establishment? Is it possible to expand NT for affiliated and dependent firms? In our opinion, nothing prevents the extension of support to small and medium sized enterprises to the entities with 100% (but not 49%) participation of the foreign equity. At the same time it is that type of exceptions from NT which practices in developed countries as well.